Vulnerability of Arctic-Boreal methane emissions to climate change - Parmentier, Frans-Jan W.; Thornton, Brett F.; Silyakova, Anna; Christensen, Torben R. (Frontiers in Environmental Science, 2024)
The rapid warming of the Arctic-Boreal region has led to the concern that large amounts of methane may be released to the atmosphere from its carbon-rich soils, as well as subsea permafrost, amplifying climate change. In this review, we assess the various sources and sinks of methane from northern high latitudes, in particular those that may be enhanced by permafrost thaw. The largest terrestrial sources of the Arctic-Boreal region are its numerous wetlands, lakes, rivers and streams. However, fires, geological seeps and glacial margins can be locally strong emitters. In addition, dry upland soils are an important sink of atmospheric methane. We estimate that the net emission of all these landforms and point sources may be as much as 48.7 [13.3-86.9] Tg CH4 yr -1 . The Arctic Ocean is also a net source of methane to the atmosphere, in particular its shallow shelves, but we assess that the marine environment emits a fraction of what is released from the terrestrial domain: 4.9 [0.4-19.4] Tg CH4 yr - 1 . While it appears unlikely that emissions from the ocean surface to the atmosphere are increasing, now or in the foreseeable future, evidence points towards a modest increase from terrestrial sources over the past decades, in particular wetlands and possibly lakes. The influence of permafrost thaw on future methane emissions may be strongest through associated changes in the hydrology of the landscape rather than the availability of previously frozen carbon. Although high latitude methane sources are not yet acting as a strong climate feedback, they might play an increasingly important role in the net greenhouse gas balance of the Arctic-Boreal region with continued climate change.